Helicobacter pylori induced interleukin-8 expression in gastric epithelial cells is associated with CagA positive phenotype. Issue 1 (January 1995) - Crabtree, J E; Covacci, A; Farmery, S M; Xiang, Z; Tompkins, D S; Perry, S; Lindley, I J; Rappuoli, R
Abstract : AIMS–To use a range of natural phenotypically variant strains of Helicobacter pylori with disparate CagA and VacA (vacuolating cytotoxin) expression to determine which bacterial factors are more closely associated with epithelial interleukin-8 (IL-8) induction. METHODS–Gastric epithelial cells (AGS and KATO-3) were co-cultured with five H pylori strains which were variously shown to express the cagA gene/CagA protein, VacA and/or to exhibit biological cytotoxicity. Secreted IL-8 was assayed by enzyme leaked immunosorbent assay (ELISA) and IL-8 messenger RNA (mRNA) was assayed using a reverse transcription polymerase chain reaction based technique (RT-PCR). RESULTS–Strains expressing CagA, including a variant strain (D931) which is non-cytotoxic and does not express the VacA protein, were found to upregulate epithelial IL-8 secretion and gene expression. In contrast, strains with no CagA expression, even in the presence of VacA and/or biological cytotoxicity, (G104, BA142), failed to induce IL-8 protein or mRNA above control values. CONCLUSIONS–These results strongly support a role for H pylori CagA or coexpressed factors other than the cytotoxin in upregulation of gastric epithelial IL-8. Increased epithelial IL-8 secretion and concomitant neutrophil chemotaxis and activation in addition to direct cytotoxicity may be an important factor in tissue damage and ulceration.